Evaluation of Biological Activity of Crude Extracts from Plants used by Indigenous Communities of Pothohar Plateau, Pakistan - Sardar, Nadia; Bibi, Yamin; Arshad, Muhammad; Ahmad, Anwaar; Zahara, Kulsoom (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2023)
The present study aimed to evaluate the potential of eight plant extracts that are used by communities of the Pothohar Plateau. Selected plants were Brassica campestris, Brassica oleracea var. italica, Allium sativum, Piper nigrum, Cinnamomum zeylanicum, Allium cepa, Olea europaea and Moringa oleifera. The antimicrobial assessment was carried out by using the agar diffusion method and antioxidant activity was evaluated using 2,2-diphenyl-1-picrylhydrazyl free radical assay, phosphomolybdate assay, and reducing power assay, against the selected isolates. Antimicrobial and growth rate studies were carried out by using two Gram-negative, one Gram-positive, and two pathogenic fungal strains. Among all tested extracts M. oleifera appeared to have the highest bioactivity with a percentage inhibition of 89 % against DPPH free radical, followed by Allium sativum 81 %, Allium cepa 75 %, Olea europaea 67 %, B. campestris 60 %, B. oleracea 58 %. During the phosphomolybdate assay similar trends were obtained such as: M. oleifera 91 % followed by A. sativum 85 %, A. cepa 78 %, Brassica campestris 72 %, Brassica oleracea 70 % and Olea europaea 65 % in higher concentration (1000 µg/ml). In the case of antibacterial assay Moringa oleifera showed maximum zone of inhibition against Staphylococcus aureus (20mm) followed by Klebsiella pneumonia (18 mm) and Escherichia coli, (17mm) whereas, crude extract of Allium sativum showed maximum zone of inhibition 14.4 mm against A. flavus whereas M. oleifera gave maximum zone of inhibition against A. alternata, followed by A. sativum and A. cepa. All the tested extracts showed bioactivities. This study can indicate the antimicrobial and antioxidant potentials of M. oleifera, and A. species. Hence, it is recommended that the extracts of these plants should be further evaluated for their possible application as antimicrobial and antioxidant agents.